Houellebecq’s Complaint. A Reading of The Elementary particles from the Notion of Masculinity in Crisis - Chaves González, Julián (2021)
This article proposes an interpretation of Michel Houellebecq’s novel The Elementary Particles from a gender perspective, focusing especially on the notion of masculinity in crisis. To this end, we criticize the premises with which the author develops his thesis on sexual liberation and we show and revise the identity implications with which his characters are constructed as men in crisis. Likewise, the article questions the place that violence occupies in Houellebecq’s work and in what sense it is provocative.